2005
DOI: 10.1111/j.1468-0297.2005.00990.x
|View full text |Cite
|
Sign up to set email alerts
|

Overconfident: Do You Put Your Money on It?

Abstract: A group exhibits overconfidence if significantly more than half the group members declare to be better than the median in some characteristic. Overconfidence was found in verbal reports for a variety of characteristics and settings but was less often studied for choice behaviour. In an experiment we tested how perceived relative skill influences verbal and choice behaviour. Treatments varied task difficulty and payment. Choice behaviour changes from overconfidence to underconfidence when the task changes from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
131
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(145 citation statements)
references
References 32 publications
11
131
2
1
Order By: Relevance
“…Empirical evidence often suggests that people tend to overestimate their abilities, yet, overconfidence seems to depend on the task, the incentives, and the techniques to elicit self-confidence. 26 To address the issue of overestimation, we next consider the average "accuracy" of the agents' guessed ranks. A meaningful measure of accuracy should take account of the fact that the group of 21 participants in the baseline treatment -which determines a subject's 'actual rank' in the experiment -is relatively small and might contain outliers.…”
Section: Resultsmentioning
confidence: 99%
“…Empirical evidence often suggests that people tend to overestimate their abilities, yet, overconfidence seems to depend on the task, the incentives, and the techniques to elicit self-confidence. 26 To address the issue of overestimation, we next consider the average "accuracy" of the agents' guessed ranks. A meaningful measure of accuracy should take account of the fact that the group of 21 participants in the baseline treatment -which determines a subject's 'actual rank' in the experiment -is relatively small and might contain outliers.…”
Section: Resultsmentioning
confidence: 99%
“…For example, many people overestimate the superiority of their work performance (Cross, 1977;Haun, Zeringue, Leach, & Foley, 2000;Zenger, 1992), social skills (College Board, 1976-1977Lewinsohn, Mischel, Chaplin, & Barton, 1980;Swann & Gill, 1997), and physical talents (Dunning, Meyerowitz, & Holzberg, 1989;Svenson, 1981; for exceptions, see Kruger, 1999;Moore, 2007). Such overconfidence persists even when the stakes are high and individuals have incentives to estimate their relative abilities accurately (Ehrlinger, Johnson, Banner, Dunning, & Kruger, 2008;Hoelzl & Rustichini, 2005;Williams & Gilovich, 2008).…”
Section: The Origins Of Overconfidencementioning
confidence: 98%
“…It is intuitive to suppose that absolute confidence will be elevated after answering a set of easy questions and lowered after answering a set of hard questions -there is some evidence supporting this intuition (e.g., Gigerenzer, Hoffrage, & Kleinbölting, 1991;Stankov, 2000). Similarly, with regard to relative confidence, research on the worsethan-average effect has shown that people commonly judge their performance to be better than average on easy tasks but worse than average on hard ones (Hoelzl & Rustichini, 2005;Moore & Kim, 2003;Windschitl, Kruger, & Simms, 2003). For these reasons we decided to use task difficulty as a means of manipulating confidence.…”
mentioning
confidence: 99%